Recent Developments in Ultrasound-Promoted Aqueous-Mediated Greener Synthesis of Biologically Vital Indole Derivatives - Choupra, Kanaram; Aheer, Ashish Kumar; Dandia, Anshu; Jain, Meenakshi; Sharma, Amit (SynOpen, 2023)
The extensive range of uses of N-heterocycles as potent bioactive motifs has attracted researchers to expand newer methods for their efficient synthesis. Particularly, indoles are widely known for their prevalent pharmacological properties. Green chemistry provides various synthetic tools viz. alternative energy resources, nonconventional solvents, nano-catalysts, etc. Modern strategies of using ultrasound as an alternative energy resource in organic synthesis has led to the development of environment friendly and cost-effective techniques. The chemical and mechanical effects of ultrasound waves impart significant enhancement in both stoichiometric and catalytic reactions. The exclusive physicochemical properties of water offer widespread utility for carrying out organic reactions in this medium. The aim of this review article is to provide an inclusive summary of the combined use of ultrasound and aqueous media for the facile synthesis of biologically vital indole derivatives.1 Introduction2 Synthesis of Biologically Vital Indoles2.1 Spirocyclic Indoles2.2 Non-spiro 3-Substituted Indoles2.3 Miscellaneous Indole Syntheses3 Conclusions
Keywords: green synthesis; indoles; aqueous medium; ultrasound; alternative energy